High performance Ag2Se films by a one-pot method for a flexible thermoelectric generator. Issue 48 (30th November 2022) - Liu, Ying; Lu, Yiming; Wang, Zixing; Li, Jiajia; Wei, Ping; Zhao, Wenyu; Chen, Lidong; Cai, Kefeng
Abstract : N-type Ag2 Se films on a nylon membrane with high thermoelectric performance and flexibility prepared by a new method. Abstract : Herein, a novel and facile method to fabricate a flexible Ag2 Se thermoelectric (TE) film on a nylon substrate is developed. The Ag2 Se film was prepared by vacuum-assisted filtration of the Ag2 Se powder synthesized by a one-pot method followed by hot pressing. An optimal Ag2 Se film shows a maximum power factor of ∼2043 μW m −1 K −2 at 300 K, which is one of the highest values reported for Ag2 Se films on flexible substrates. The excellent performance of the film is mainly due to the high density and good crystallinity of Ag2 Se grains with semi-coherent and coherent grain boundaries. Besides, the film also shows good flexibility. Furthermore, a 6-leg flexible TE generator (f-TEG) assembled from the optimal film produces a maximum power of ∼9.14 μW (corresponding power density of ∼30.46 W m −2 ) at a temperature gradient of 30.3 K, which proves that the film has exceptionally high TE properties. This work presents a simple, fast, low cost and environmentally friendly synthesis process for preparation of high performance Ag2 Se-based flexible TE films.